Short Communication: Effect of cryopreservation on ultrastructure and mitochondrial function of albino Pangasius catfish spermatozoa (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hasanah U, Binawanto, Alimuddin A, Boediono A, Kursini E. 2020. Short Communication: Effect of cryopreservation on ultrastructure and mitochondrial function of albino Pangasius catfish spermatozoa. Biodiversitas 21: 4524-4528. Cryopreservation techniques have been carried out on many endangered species and animals with unique characteristics. Successful cryopreservation techniques vary between species depending on various factors. The study used cryopreserved spermatozoa of the albino Pangasius catfish as samples. The cryopreserved spermatozoa were analyzed by its ultrastructure, functional mitochondria, and viability. The cryopreservation was performed using a combination of 10% methanol, skim milk, and fish ringer extender. A deep freezer is used for cryopreservation at -80 °C with a storage period of 14 days. Observations were made on fresh spermatozoa, post-equilibration spermatozoa, and frozen-thaw spermatozoa. This study found there were differences in ultrastructure and morphology in the three treatments. Fresh spermatozoa and post-equilibration spermatozoa appeared intact membrane, mitochondrial, and flagellar structures. In contrast, in frozen-thaw spermatozoa, there was damage to the cell membrane. The study showed different percentages of yields on functional mitochondria of fresh spermatozoa (98 ± 2%), spermatozoa post-equilibration (57 ± 7%), frozen-thaw spermatozoa (42 ± 3.21%). Cell viability showed that there were differences in viability of fresh spermatozoa and frozen-thaw (p
Keywords: Albino Pangasius catfish, cryopreservation, mitochondrial function, spermatozoa, ultrastructure